Os exercícios de criação de J. H. Koellreutter: um estudo de sua aplicação na escola regular - Santos, Marcos Paulo Miranda Leão dos (2015)
This paper relates with the importance of creation for the musical student learning. We start from the problem: How the musical creation exercises proposed by Koellreutter would be accepted by students from a public school? Would the exercises be able to achieve those goals? The proposed Koellreutter would fit the peculiar physical structure of a public elementary school? Some publications have addressed the importance of compositional activities to integrate the development, but there is still a lack in academic studies aimed to create exercises and their reflection in the development of children and youth. However, renowned authors such as Schafer, Gainza, Beineke, Swanwick, Moraes, have already been addressing the importance of education grounded in musical creation, we restrain ourselves in the creation exercises proposed by the composer and educator JH Koellreutter. Our objective was to investigate whether the activities could contribute to music education processes when inserted in the school environment. The B class of the 6th grade of the Primary School Journalista Durval Aires, located in Maracanaú was elected as a field of study. The methodology developed within the qualitative approach, an action/research, in which, eight creative activities sections were experienced with the students. The record of the meetings was through audiovisual recording, besides the construction of a diary. As a result, we realized that the activities developed by Koellreutter, even with the difficulties encountered, were well accepted by the students and it was provided to them the pleasure of performing, appreciation and especially the music-making students.